Odpowiedzi

2009-12-18T16:07:38+01:00
2(n-3)(n-2)(n-1)n - (n-2)(n-1)n(n+1)
----------------------------------------- =
24

2(n^2 - 2n - 3n + 6)(n^2 -n) - (n^2 -n -2n +2)(n^2 +n)
-------------------------------------------------------------- =
24


2(n^2 - 5n +6)(n^2 - n) - ( n^2 - 3n + 2)(n^2 +n)
------------------------------------------------------------=
24

2(n^4-n^3-5n^3+5n^2+6n^2-6n)-(n^4+n^3-3n^3-3n^2+2n^2+2n)
----------------------------------------------------------------
24

2(n^4 - 6n^3 + 11n^2 -6n) - ( n^4 - 2n^3 -n^2 + 2n)
----------------------------------------------------------------
24

2n^4 - 12n^3 + 22n^2 - 12n - n^4 + 2n^3 +n^2 -2n
---------------------------------------------------------
24

n^4 - 10n^3 +24n^2 -2n
----------------------------- =
24


n^2(n^2 - 10n + 24) -2n
----------------------------- =
24

2009-12-18T16:11:54+01:00
2(n-3)(n-2)(n-1)n - (n-2)(n-1)n(n+1) (kreska ułamkowa przez całe i w) mianowniku 24
= 2(n^2-2n-3n+6)(n^2-n)- (n^2-2n)(n^2-1)(kreska ułamkowa przez całe i w) mianowniku 24
= 2( n^4+n^3-2n^3+2n^2-3n^3+3n^2+6n^2-6n) -(n^4-n^2-2n^3+2n)(kreska ułamkowa przez całe i w) mianowniku 24
= 2n^4+2n^3-4n^3+4n^2-6n^3+6n^2+12n^2-12n-n^4+n^2+2n^3-2n
(kreska ułamkowa przez całe i w) mianowniku 24
= n^4-6n^3+23n^2-14n(kreska ułamkowa przez całe i w) mianowniku 24
= n(n^3-6n^2+23n-14)(kreska ułamkowa przez całe i w) mianowniku 24
=